Pengembangan Budaya Religius Dalam Pembinaan Kecerdasan Spiritual Siswa - Maulana, Iqbal Alan; Syafi’i , Imam (Cendekia : Jurnal Pendidikan dan Keagamaan, 2024)
The research objectives to describe the process of developing religious culture in fostering students' spiritual intelligence. To find out the forms of developing religious culture in developing students' spiritual intelligence. And t o describe the factors that influence the development of religious culture in developing students' spiritual intelligence. This research uses a qualitative approach with a descriptive qualitative research type. Data collection techniques using observation, interviews and documentation. The data analysis technique uses the interactive Miles, Huberman, and Saldana method with the steps: data condensation, data presentation, and drawing conclusions. The process of developing a religious culture internalization, socialization, and enculturation. Forms of developing religious culture include: religious climate, religious habituation and a culture of smiling greetings. Factors supporting the development of religious culture at MTs Zainul Hasan Balung are going well, both support from schools, parents and the environment. While the inhibiting factors have not been resolved properly due to limited facilities and infrastructure.